Post-Islamisme? Mobilisasi Politik Partai Islam di Bali Dalam Pemilihan Umum Legislatif - Pradhananta, Ilham Azhimi; -, Bandiyah; Ali Azhar, Muhammad (Jurnal Nawala Politika, 2021)
Islamic parties as minority parties in Bali have their own challenges based on the results of the 2004-2019 legislative elections. The purpose of this study is to find out the inhibiting factors for political parties lead to low election vote results. This study uses Stefano Bartolini's theory and Asef Bayat's post-Islamism ideology. The research method used comparative qualitative methods using primary data and secondary data  to identify and describe the various attitudes of Islamic political parties in their dynamics.The results of this study show: First, Islamic political parties in Bali are still institutionally weak, thus hinders political party to practice political mobilization effectively. Second, Islamic political parties in Bali nowadays are relying on figures with a strong mass base network from Islamic foundations such as PKS and PPP. Third, the political party conflicts that occurred internally, greatly influenced the results of the 2019 Denpasar City Election. Keywords: Political mobilization, Islamic political parties, legislative elections, social cleavage